2014
DOI: 10.1111/fwb.12499
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of Cladocera and Copepoda from lakes of contrasting temperature

Abstract: Summary We studied the fatty acid (FA) composition of six species of Cladocera and six species of Copepoda from five cold‐water lakes, situated in the tundra and/or in the mountains, and eight species of Cladocera and four species of Copepoda from eight warm‐water lakes (including one reservoir) in temperate regions. We asked whether the contrasting temperature would result primarily simply in changes in the percentages (i.e. percentage of total FAs) and absolute contents (quantities) of the long‐chain polyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 87 publications
2
40
1
Order By: Relevance
“…However, the results of correlative field studies are controversial: correlations over 3 years within a single lake revealed a decrease of EPA in Daphnia with temperature (McMeans et al, 2015), while a comparison of 13 warm and cold lakes yielded no correlation of Daphnia EPA content with water temperatures (Gladyshev et al, 2015). Experimental studies provide a more consistent picture on the effects of temperature on the EPA-content of Daphnia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of correlative field studies are controversial: correlations over 3 years within a single lake revealed a decrease of EPA in Daphnia with temperature (McMeans et al, 2015), while a comparison of 13 warm and cold lakes yielded no correlation of Daphnia EPA content with water temperatures (Gladyshev et al, 2015). Experimental studies provide a more consistent picture on the effects of temperature on the EPA-content of Daphnia.…”
Section: Discussionmentioning
confidence: 99%
“…The filters were air-dried for about 30 min, then placed into chloroform-methanol, and frozen at 2208C until laboratory analysis. Lipids were extracted by chloroformmethanol (2 : 1, v/v) using the protocol described in (Gladyshev et al 2010(Gladyshev et al , 2015. Briefly, lipids were extracted by chloroform-methanol (2 : 1, v/v) three times.…”
Section: Analyses Of Fasmentioning
confidence: 99%
“…Temperature is also known to influence phyto-and zooplankton composition in most waters (Dahlgren, Wiklund, & Andersson, 2011;Perhar, Arhonditsis, & Brett, 2012). Recently demonstrated is that the fatty acid lake profiles of cladoceran and copepod are affected by contrasting temperatures (Gladyshev et al, 2014). Differences in planktonic communities in turn influence the fatty acid composition of small fish species that feed on these plankton (Arts, Ackman, & Holub, 2001;Galloway et al, 2014;Petursdottir, Gislason, & Falk-Petersen, 2008).…”
Section: Discussionmentioning
confidence: 99%